Synthesis of Zeolitic imidazolate frameworks‐8@ layered double hydroxide polyhedral nanocomposite with designed porous voids as an effective carrier for anti‐cancer drug‐controlled delivery - Azita Dilmaghani; Kamran Hosseini; Vahideh Tarhriz; Vahid Yousefi (IET Nanobiotechnology, 2023)
Abstract In nanotechnology, compounds containing metal materials are used in pharmaceutical sciences. The main purpose of this research was to introduce a novel method to control the amount of zeolite imidazolate framework (ZIF) in water by forming a protective layer such as layered double hydroxide (LDH). Firstly, ZIF was synthesised as the nucleus of the nanocomposite, and then LDH was formed by in situ synthesis as a protective layer. Scanning electron microscope, Fourier‐transform infrared spectroscopy, X‐Ray Diffraction, and Brunauer, Emmett and Teller techniques were used to determine (ZIF‐8@LDH chemical structure and morphology. Our findings revealed that the ZIF‐8@LDH‐MTX complex could interact with carboxyl groups and trivalent cations by creating a bifurcation bridge, clarity, and high thermal stability. The antibacterial test indicated that ZIF‐8@LDH was able to inhibit pathogenic growth. 2,5‐Diphenyl‐2H‐Tetrazolium Bromide assay results showed that ZIF‐8@LDH alone had no notable cytotoxic effect on Michigan Cancer Foundation‐7 (MCF‐7) cancer cells. However, the cytotoxicity rate was significantly increased in treated MCF‐7 cells with ZIF‐8@LDH‐MTX compared to that of treated cells with methotrexate alone, which can be reasoned by the protection of drug structure and increasing its permeability. The drug release profile was constant at pH = 7.4. All findings indicated that the ZIF‐8@LDH complex could be considered a newly proposed solution for effective anti‐cancer drug delivery.